CULTURAL ADAPTATION AND SOCIAL EXPERIENCE INTERNATIONAL STUDENT - Zuhroh, Ni'matuz; Susilawati, Samsul; Rahmaniah, Aniek; Sari, Ulfi Andrian (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
This study seeks to answer the question of how the process of cultural adaptation and social experience of international students. Research on cultural adaptation and social experience that occurs in international students in Malang City uses a qualitative research type. Data were obtained through observation and in-depth interviews with international students. The next process after the interview is the transcription of the data. In analyzing and interpreting data, this research uses an empirical phenomenological approach. The results of this study found several challenges of cultural adaptation faced as follows: 1) Barriers to communication adaptation and interpersonal interaction, related to the mastery of Indonesian, the use of mixed languages in the local community, as well as aspects of cultural values in communication. 2) Barriers to adaptation to differences in food choices and tastes. 3) The gap in cultural values or culture shock between habits and home culture with habits and host culture. 4) Barriers to adaptation to multi-cultural demographics: meeting and interacting with various people on campus and Malang City consisting of various tribes, nations, ethnicities, and races. 5) Barriers to institutional and bureaucratic adaptation, such as not yet optimal language programs and cultural introductions and low efficiency in administrative and bureaucratic services. 6) Barriers to the cultural adaptation competence of the individual sojourner himself.